Analisis Kemampuan Penulisan Kalimat Efektif Mahasiswa di Universitas Bhayangkara Jakarta Raya - Zulfadhli, Muhammad; Hamdani, Haris; Rebecca Lakawa, Agustin (GERAM: Gerakan Aktif Menulis, 2022)
Writing effective sentences is an important skill to be mastered. However, obstacles still are found among university students. This study aims to analyze and describe the student’s ability to compose sentences effectively while writing at Universitas Bhayangkara Jakarta Raya. This research used qualitative research. The research conducted was at Universitas Bhayangkara Jakarta Raya, Bekasi City. The subjects of this study consisted of 34 undergraduate students who studied the general introductory course of the Indonesian language. The data was collected through an effective sentence writing ability test, observation, and interviews. The data analysis technique used Miles and Huberman analysis, which consisted of four stages: data collection, data reduction, data display, and verification or data conclusion. The results show that the achievement of students' ability of effective sentence writing was generally in a good category. in another side, several students still had not mastered all indicators of effective sentence writing. The aspect of diction is the most mastered by students, while the aspect of reasoning (logical) is the most challenging aspect for students. Student's difficulties in writing effective sentences were found in 4 indicators, including 32% in the grammatical aspect, 41% in the reasoning aspect, 24% in the economic aspect, and 35% in the parallelism aspect. The results of this study imply that learning effective sentence writing still needs to be improved in higher education, so the proper learning of Indonesian language courses is needed.